Association between dialysate sodium concentration and interdialytic weight gain in patients undergoing twice weekly haemodialysis - Manji, Soraiya (BMC Nephrol, 2021)
BACKGROUND: Chronic kidney disease is highly prevalent across the globe with more than 2 million people worldwide requiring renal replacement therapy. Interdialytic weight gain is the change in body weight between two sessions of haemodialysis. Higher interdialytic weight gain has been associated with an increase in mortality and adverse cardiovascular outcomes. It has long been questioned whether using a lower dialysate sodium concentration during dialysis would reduce the interdialytic weight gain and hence prevent these adverse outcomes. METHODS: This study was a single blinded cross-over study of patients undergoing twice weekly haemodialysis at the Aga Khan University Hospital, Nairobi and Parklands Kidney Centre. It was conducted over a twelve-week period and patients were divided into two groups: dialysate sodium concentration of 137 meq/l and 140 meq/l. These groups switched over after a six-week period without a washout period. Univariate analysis was conducted using Fisher’s exact test for categorical data and Mann Whitney test for continuous data. RESULTS: Forty-one patients were included in the analysis. The mean age was 61.37 years, and 73% were males. The mean duration for dialysis was 2.53 years. The interdialytic weight gain was not significantly different between the two groups (2.14 for the 137 meq/l group and 2.35 for the 140 meq/l group, p = 0.970). Mean blood pressures were as follows: pre-dialysis: DNa 137 meq/l: systolic 152.14 ± 19.99, diastolic 78.99 ± 12.20, DNa 140 meq/l: systolic 156.95 ± 26.45, diastolic 79.75 ± 11.25 (p = 0.379, 0.629 respectively). Post-dialysis: DNa 137 meq/l: systolic 147.29 ± 22.22, diastolic 77.85 ± 12.82 DNa 140 meq/l: systolic 151.48 ± 25.65, diastolic 79.66 ± 15.78 (p = 0.569, 0.621 respectively). CONCLUSION: There was no significant difference in the interdialytic weight gain as well as pre dialysis and post dialysis systolic and diastolic blood pressures between the two groups. Therefore, using a lower dialysate sodium concentration does not appear useful in altering the interdialytic weight gain or blood pressure although further studies are warranted with a larger sample size, taking into account residual renal function and longer duration for impact on blood pressures.